A moisture-tolerant route to unprotected α/β-amino acid N-carboxyanhydrides and facile synthesis of hyperbranched polypeptides - Zi-You Tian (Nature Portfolio, 2021)
Synthetic polypeptides are biomimetic materials that are commonly prepared by ring-opening polymerization of amino acid N-carboxyanhydrides (NCAs), but the methods for NCA synthesis usually require anhydrous and air-free conditions. Here, the authors report a method for the synthesis of NCAs under atmospheric conditions and room temperature, based on the use of epoxides as acid scavengers.